TRANSFORMASI PEMBELAJARAN MATEMATIKA BERBASIS LMS MENUJU SEAMLESS LEARNING DALAM MENDUKUNG SDG 4 DI SMP X KABUPATEN MAGETAN - Zaenal Abdul Rahmandani; Karmila Putri; Muhammad Yusron Lutfi; Anggun Nainggolan; Brillian Aldiva Yunan Ichnaton; Narelia Rizky Oktadivani; Adhitya Amarulloh (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
The purpose of this study is to examine how the Learning Management System (LMS) helped Junior High School X in Magetan Regency adopt Seamless Learning in mathematics instruction during the 2024–2025 academic year. The difficulties of learning abstract mathematics and the necessity of digital change in education serve as the foundation for this study. Teachers and students are the research subjects in this qualitative study that uses a case study technique. Observation, interviews, and LMS activity analysis are methods of gathering data that are subsequently subjected to theme analysis. The findings show that the LMS functions as a learning monitoring tool that promotes ongoing learning, a venue for interaction, and a medium for information distribution. The LMS's adoption has been successful in raising student engagement, learning autonomy, and comprehension of mathematical concepts. Additionally, the LMS makes it easier to integrate learning across formal and informal contexts, as well as online and offline, which is a crucial aspect of seamless learning. The Sustainable Development Goals (SDGs), especially SDG 4 on Quality Education, which highlights the significance of inclusive, equitable, and technology-based access to education, are in line with these findings. As a result, using LMS can be a successful tactic for raising the standard of math instruction in the digital era.